Principles of macroeconomics - Mankiw, N. Gregory (Cengage Learning, 2015)
"PRINCIPLES OF MACROECONOMICS, Seventh Edition, continues to be the most popular and widely-used text in the economics classroom. Instructors find it the perfect complement to their teaching. A text by a superb writer and economist that stresses the most important concepts without overwhelming students with an excess of detail was a formula that was quickly imitated, but has yet to be matched. The seventh edition features dozens of new applications that emphasize the real-world relevance of economics for today's students through interesting news articles, realistic case studies, and engaging problems. A thorough update has been made to keep all chapters fresh and relevant with current Economic coverage. A new Quick Check Multiple Choice section has been included to round out the end-of-chapter offering. Intended as a deeper dive into the material than the existing Questions for Review, these Quick Check Multiple Choice Questions and Problems and Applications will be directly lifted into the Mankiw Aplia product. Aplia, the best-selling online homework solution, will be available with new enhancements that include accessibility on mobile devices, improved graphing experience, a new interactive ereader with videos and graphing tutorials, and much more. The seventh edition premier ancillary package is the most extensive in the industry, using a team of instructors/preparers that have been with the project since the first edition"--Provided by publisher.